Loading of cast supporting structures of three-piece bogie 18-100 in the presence of defects on the surface of wheel rolling - O. G. Krasnov; G. S. Nozdrachev; А. S. Gasyuk (Вестник Научно-исследовательского института железнодорожного транспорта)
Results of the loading study of support structures of bogies 18 - 100 with the presence of defects in the form of slides and uneven wheel wear on the rolling surface were shown. Research carried out by strain measurement. Strain gauges were installed in the area of spring and axle boxes openings of the side frames and bolster. Defects on the rolling surface formed at VNIKTI test site. Wheelset with defects rolls instead of the first wheelset in one of the bogies which was considered experimental. Stress levels are defined at values 1 and 3 mm for the sliders, 2 and 4 mm for uneven rolling. Trial runs were conducted during experimental train motion on direct track section, as well as on turnouts of 1/11 mark, when turning to a side track and in a curve of 600 m radius, at a speed range 30 to 100 km/h both forward and reverse. Stress levels in the most loaded areas of the side frame and bolster were set experimentally. It was shown that defects with limit-exceeding geometric parameters are a huge source of force loading of axle box openings of the side frames. The remaining areas of side frames and bolsters experience additional loading during dynamic impact interaction with the wheel defects and the rail, but the stress levels at these locations is 2 - 3 times lower than in the zone adjacent to the defective wheel. It was found that for the fatigue resistance of the side frames exploitation of cars with slides more than 3 mm is not allowed. During uncoupling of cars, when wheel with slides more than 3 mm is detected, it needs to carry out flaw detection of side frames by NDT methods.